مسؤولية الغير عن الاعتداء الذي يقع على نظام بطاقة الائتمان - العروسي, حاقة (University of Eloued جامعة الوادي, 2020)
نا من خلال هذا المقالإلى مختلف الجرائم الناشئة عن الاستعمال غير المشروع لبطاقات الائتمان من جانب الغير، فالحامل الشرعي في هذا الموقع هو منصدرت البطاقة لصالحه وباسمه، وفي هذه الفرضية يقوم الغيرممن لا يخولهم حامل البطاقة أو من صدرت البطاقة لصالحه باستخدامها خلافا لإرادته، والحالات المتصور وقوعها في هذه الحالة هي قيام الغير باستخدام البطاقة الائتمانية بعد سرقتها أو فقدانها من قبل الحامل الشرعي للبطاقة، أو بعد التلاعب في مكونات البطاقات الائتمانيةسواء المادية أو المعنوية. In this article, we tried to address the various crimes resulting from the illegal use of credit cards by third parties. The legitimate holder in this case is the person who the card was issued in his favor and under his name. Under this hypothesis, the third party are those who are not authorized by the cardholder or who are using the card against the will of whoever the card was issued for. The cases in which this could happen are the use of a credit card by others after theft or loss of the card from its legitimate owner, or after manipulating the moral or materiel elements of the credit card.
مجلد11، عدد1
Keywords: ل البطاقة؛التزوير؛بطاقةالائتمان؛الجرائم؛الحامل غير الشرعي للبطاقة; Card holder; Counterfeiting; Credit Card; Crimes; Illegal card holder